Пристрій для буріння свердловин без подавання охолоджуючої рідини на вибій - Вировець, Л.М.; Лукаш, В.А. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The paper deals with a construction of an experimental sample of a device for drilling holes in difficult media, in which a cutting tool is cooled and products of breaking are removed without delivery of a liquid into a bottom hole.